PERSEPSI PETUGAS LAPANGAN KELUARGA BERENCANA, PROVIDER, DAN PASANGAN USIA SUBUR TERHADAP EKSISTENSI PROGRAM KELUARGA BERENCANA PADA ERA DESENTRALISASI DI KABUPATEN KARANGASEM - Sudibia, I Ketut; Marhaeni, A.A.I. N (PIRAMIDA; Vol 3, No.2 Desember 2007, 2012)
The change of government from “The New Order” to “The Reformation Order” has also been followed by the change of administration system from centralization to decentralization system. Along with that change, the authority and institution of family planning program have also been transferred to the regency or city government. These changes have risen various perceptions in term of the institutional, roles, and functions of that institute. Other important changes include that (1) the family planning coordination board organization on regency level did not change but the echelon was decreased; or (2) the family planning coordination board organization on regency level was merged to other institution; or (3) the family planning coordination board activity on regency level is only a little part of the other instance. All of those changes have caused some problems of coordination from family planning coordination board on province level to regency level, and it has given a negative impact to the family planning program achievement.The objectives of this study are to investigate (1) the perception of the family program field worker to the existence of family planning program in the decentralization era; (2) the perception of the family planning fieldworkers to the realization of duties in the decentralization era; (3) the perception of the provider to the existence of family planning program in the decentralization era; (4) the perception of the eligible couple to the existence of family planning program in the decentralization era; and (5) the perception of the interrelated decision makers to the existence of family planning program in the decentralization era.This study was carried out in the Regency of Karangasem with total respondent of 153 persons, that consist of 46 fieldworkers; 89 eligible couples, 12 providers, and 6 interrelated decision makers. Some sampling techniques used in this study are; simple random sampling for family planning fieldworker, stratified random sampling for eligible couple, and purposive sampling for the provider and the interrelated decision maker. Data are collected using the structured interview, in-depth interview, and observation method. Then data are analyzed using descriptive and inferential statistics.The conclusion of this study are (1) the family planning field workers who have duty in front line felt the decrease of funding support and the intention of regency government; (2) the number of family planning fieldworkers in decentralization era have been decreased, because part of them have been transferred to the other institution; (3) the providers also felt that the funding support and the intention of government decreased in decentralization era; (4) the eligible couples felt that activities related to increasing family income have also decreased such as business partnership, capital aid, and productive economic creation; and (5) the perception of the interrelated decision makers also show that the funding support and the intention of regency government has been decreased.Based on those conclusions, some suggestions are proposed, such as (1) to maintain the sustainability of the family planning program in the decentralization era, high commitment from the government, especially the regency government are needed; (2) the regency government should provide a routinely budget for maintaining the sustainability of the family planning program; (3) the family planning fieldworkers as front liner are suggested not to be transferred to other departments (4) the service centers need to be encouraged to increase communication, information, and education of the eligible couple, and other activities; and (5) the regencygovernment need to provide capital aid, business partnership, and productive economic creation for the poor households.
Keywords: family planning coordination board, eligible couples, family planning fieldworkers